Interpretation and Validation of Maximum Absorbance Data Obtained from Turbidimetry Analysis of Plasma Clots - Pieters, Marlien; Guthold, Martin; Nunes, Claudia M.; de Lange, Zelda (Thrombosis and Haemostasis, 2020)
Turbidimetry is used to characterize fibrin clot properties. In purified systems, maximum absorbance (MA) directly relates to fibrin fiber cross-sectional area. However, in plasma samples there are discrepancies in the relationships between MA and fibrinogen concentration, fiber diameter, other clot properties, and cardiovascular disease outcomes, which complicate data interpretation. This study aims to advance understanding of MA of plasma clots through testing how well it relates to fundamental dependence on fibrinogen concentration and fiber diameter as predicted by light scattering theory, other clot properties and lifestyle, and biochemical variables. Plasma samples from 30 apparently healthy individuals with a fibrinogen concentration from 2.4 to 6.4 g/L were included. We performed turbidimetry, permeability, scanning electron microscopy, and rheometry on in vitro formed plasma clots. MA correlated more strongly with fibrinogen concentration (r = 0.65; p < 0.001) than with fiber diameter (r = 0.47; p = 0.01), which combined explained only 46% of the MA variance. Of additional variables measured, only low-density lipoprotein cholesterol correlated with MA (r = 0.46; p = 0.01) and clot lysis (r = 0.62; p < 0.0001) but not with fiber diameter or fibrinogen concentration. MA correlated with clot lysis time (r = 0.59; p = 0.001), storage modulus (r = 0.61; p = 0.001), and loss modulus (r = 0.59; p = 0.001), and negatively with clot permeability (r = –0.60; p = 0.001) also after adjustment for fibrinogen concentration and fiber diameter. Increased MA is indicative of a prothrombotic clot phenotype irrespective of fibrinogen concentration. MA is more indicative of overall clot density than of fiber diameter. Other plasma components can alter internal fiber density without altering fiber diameter and should be considered when interpreting MA of plasma samples.
Keywords: turbidimetry; fibrinogen; fibrin structure; fibrin viscoelastic properties; blood plasma samples